2021
DOI: 10.1016/j.ultsonch.2020.105371
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of nonspherical bubble in compressible liquid under the coupling effect of ultrasound and electrostatic field

Abstract: Highlights Enhancement effect of electrostatic field on ultrasonic cavitation is explained. Model for a nonspherical bubble in compressible liquid under the coupling effect of ultrasound and electrostatic field was developed. Effect of different electric field strengths on the bubble cavitation was analyzed theoretically. We compared gas pressure, temperature and cavitation threshold with and without electric stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…The work of Shan et al 26 also determined a similar behaviour of cavitation bubbles in an electric field using underwater pulsed discharge. Another work by Deng et al 27 determined similar results using ultrasound induced cavitation. Table 2 lists the values of the actual differences in R M between 0 V m À1 and 3000 V m À1 for all of the target-liquid combinations.…”
Section: Cavitation Bubble Evolution Under An External Electric Fieldmentioning
confidence: 60%
See 1 more Smart Citation
“…The work of Shan et al 26 also determined a similar behaviour of cavitation bubbles in an electric field using underwater pulsed discharge. Another work by Deng et al 27 determined similar results using ultrasound induced cavitation. Table 2 lists the values of the actual differences in R M between 0 V m À1 and 3000 V m À1 for all of the target-liquid combinations.…”
Section: Cavitation Bubble Evolution Under An External Electric Fieldmentioning
confidence: 60%
“…While previous works have analysed the phenomena of cavitation influenced by an external electric field, these works employed different techniques for the generation of cavitation such as underwater pulse discharge, 26 and ultrasound induced cavitation. 27 The technique of electric-field assisted laser ablation in liquids (EFLAL) has recently gained prominence for the synthesis of nanoparticles of a variety of morphologies. [28][29][30][31][32][33][34][35] However, these works have also not addressed the issue of the behaviour of laser-induced cavitation bubble dynamics influenced by an external electric field.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were found in Lind's theoretical analysis of non-spherical bubbles in a magnetic liquid, [27] and it is also supported by violent bubble oscillation manipulated by external fields in a magnetic fluid [28,29] and electric medium. [43] Moreover, after removing the ultrasonic field at 6.5 µs, damping oscillations of MMBs are also displayed, and the final static radius is increased with the intensity of magnetic field.…”
Section: Pulsation In Unbound Casementioning
confidence: 96%
“…The derivations of equations ( 10) and ( 11) (see Ref. [3]) are based on the assumption that ultrasonic wave propagates within an infinitely large liquid region. Hence, no standing wave occur in the liquid.…”
Section: Derivation Of the Theoretical Modelmentioning
confidence: 99%
“…They found that the yield of flavonoids was 10% higher using UEE than conventional ultrasound extraction, and it was 18% higher than water bath extraction. A work by Yang et al [3] reveals the mechanism how electric stress strengthens ultrasonic cavitation. However, many details of interactions between nonspherical bubbles are not known.…”
Section: Introductionmentioning
confidence: 99%